Beyond The Skin Barrier: How Transfersomes and Transethosomes are Revolutionizing Topical Therapies - Widayanti Supraba; Husni, Patihul; Chaerunisaa, Anis Yohana (Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction: The fundamental challenge of effective skin permeation has long limited the therapeutic potential of topical drug delivery systems. Conventional formulations frequently fail to achieve adequate penetration through the skin barrier, necessitating innovative approaches to enhance drug bioavailability while maintaining targeted delivery to specific skin layers. Aims: This review evaluates the transformative impact of transfersomes and transethosomes as advanced nanovesicular systems designed to overcome traditional limitations in topical drug delivery. Methods: The review examines ultra-deformable nanovesicle technologies through comprehensive analysis of their operational mechanisms, including osmotic gradient exploitation in transfersomes and ethanol-facilitated lipid fluidization in transethosomes. Performance comparisons with conventional formulations across various therapeutic applications were conducted to assess clinical efficacy and delivery capabilities. Result: These nanovesicular systems demonstrate superior performance in delivering diverse therapeutic agents to targeted skin layers while effectively minimizing systemic absorption. The analysis reveals significant advantages over traditional formulations, with enhanced penetration capabilities that extend to macromolecular therapeutics and biologics when integrated with complementary technologies such as microneedle arrays and iontophoresis. Current research developments focus on addressing existing limitations through lyophilization techniques, hybrid polymer systems, and advanced manufacturing processes. Conclusion: Transfersomes and transethosomes represent a significant advancement in topical drug delivery technology, offering promising solutions to longstanding permeation challenges. The future trajectory toward personalized formulations and sustainable production methods using plant-derived components indicates their potential to fundamentally redefine treatment approaches in dermatology, oncology, and pain management, establishing minimally invasive yet highly effective therapeutic options as the standard in patient care.